Preparation method of trace aluminum doped high purity quartz sand
Patent Information
- Application Number
- CN202510556656.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
但铝元素在石英砂中的分布均匀性仍有待提升,且工艺流程较为复杂
[0024](1)本发明通过离心工艺获取氧化铝溶液,利用氧化铝极微溶于水且在水中高分散的特性,以氧化铝水溶液同时作为极微量的铝元素掺杂源及水解反应池,使得硅源在水解反应时不断与水中的氧化铝结合,从而保证了含Al官能团在溶液中的均匀分散性,避免了一些其余铝源在溶解过程中直接发生水解形成氧化铝胶粒或聚集体的可能。另外,也降低了在称量铝源材料阶段对于高精密仪器的需求,提高了取样精度与稳定性。
Smart Images

Figure CN123002864A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-purity quartz sand preparation technology, specifically to a method for preparing high-purity quartz sand with trace amounts of aluminum doping. Background Technology
[0002] High-purity quartz sand refers to micron-sized quartz particles with a SiO2 content of not less than 99.99% and extremely low impurity element content. Due to its excellent chemical stability, extremely low coefficient of volume expansion, and high insulation and voltage resistance, high-purity quartz sand has become the material basis for manufacturing high-end products in the silicon industry.
[0003] Currently, high-purity quartz sand is mainly prepared and produced through two methods: one is the purification method of natural quartz ore, and the other is the high-purity silicon source sol-gel method. Due to the abundance of raw materials and the low production cost, the purification method of natural quartz ore dominates in terms of overall market size and production capacity. However, the purification method of natural quartz ore still faces the following difficulties: (1) The method is subject to certain limitations in terms of raw materials; (2) Since the purified natural sand still contains a small amount of impurities, it is only suitable for photovoltaic and general electronic device fields that can tolerate trace impurities and do not pursue ultra-high purity, and is not suitable for semiconductor or optical fiber fields that require extremely high purity; (3) Natural quartz sand has high hardness, and its particle size and shape are difficult to control. In contrast, the high-purity silicon source sol-gel method uses a high-purity silicon source as a precursor. Through a sol-gel process, silica gel is generated via hydrolysis and condensation reactions. High-purity quartz sand is then obtained through drying and heat treatment. This method allows for control over impurity content, enabling the synthesis and production of ultra-high purity (e.g., 6N grade) quartz sand. Furthermore, the synthesized quartz sand has relatively low hardness, and its particle size and shape are more uniform. However, currently, the high-purity silicon source sol-gel method faces practical challenges such as high preparation costs, complex synthesis processes, and difficulties in large-scale industrial production. This limits its production to small-batch production to meet the demands of the high-end market with extremely high purity requirements.
[0004] To further improve the structural stability of quartz materials under high-temperature conditions, trace amounts of aluminum can be doped into high-purity quartz sand. For example, patent application CN109467306A describes a post-processing method to incorporate aluminum into high-purity quartz sand. However, the aluminum incorporated in this method simply adheres to the surface of the quartz sand, resulting in uneven distribution and the crystallization of impurities.
[0005] For example, patent application CN116715243A discloses a method for preparing aluminum-doped silica sand, including the following steps: removing impurities from aluminum sol and silicon source respectively to obtain impurity-removed aluminum sol and silicon source; mixing the impurity-removed aluminum sol with water, then adding the impurity-removed silicon source and acidic catalyst to carry out a hydrolysis reaction to obtain aluminum-doped silica sol; subjecting the aluminum-doped silica sol to a first heating treatment, then adjusting the pH value to 7.5-12 to obtain a gel; wherein the temperature of the first heating treatment is higher than the temperature of the hydrolysis reaction; and subjecting the gel to drying, calcining, and a second heating treatment in sequence to obtain aluminum-doped silica sand. However, the uniformity of aluminum distribution in silica sand still needs to be improved, and the process is relatively complex. Summary of the Invention
[0006] To address the aforementioned technical problems in the existing technology, this invention provides a method for preparing high-purity quartz sand doped with trace amounts of aluminum, wherein trace amounts of aluminum are doped during the synthesis process to improve the high-temperature resistance of the quartz sand.
[0007] A method for preparing high-purity quartz sand with trace amounts of aluminum doping includes the following steps:
[0008] S1. Mix the silicon source and solvent evenly to obtain the precursor solution;
[0009] S2. Mix alumina and ultrapure water, centrifuge, take the supernatant, and filter the supernatant through a filter membrane to remove undissolved alumina particles and obtain an alumina solution.
[0010] S3. Detect the concentration of aluminum in the alumina solution;
[0011] S4. Dilute the alumina solution after detection in step S3 according to the target doping amount;
[0012] S5. Take the diluted alumina solution from step S4 and add it to the precursor solution obtained in step S1. Mix and stir to allow hydrolysis to occur and form a sol.
[0013] S6. Add a catalyst to the sol to obtain a gel;
[0014] S7. The gel is aged, and then the water in the gel is replaced with the same solvent as in step S1. The gel is then dried, calcined, and ground to obtain the trace aluminum-doped high-purity quartz sand. The aluminum doping concentration in the trace aluminum-doped high-purity quartz sand is 3-229 ppm.
[0015] Preferably, in step S1, the silicon source is tetramethyl or tetraethyl orthosilicate, and the solvent is ethanol, methanol, or acetone.
[0016] Preferably, the pore size of the filter membrane is 10 μm.
[0017] Preferably, the volume ratio of the silicon source in step S1 to the diluted alumina solution added in step S5 is 1:1-4. More preferably, the volume ratio of the silicon source in step S1 to the diluted alumina solution added in step S5 is 1:4. At this ratio, the hydrolysis reaction is more uniform, the nanoparticles in the final gel are smaller, the gel skeleton is finer, and the surface smoothness of the dry gel particles is higher.
[0018] Preferably, the hydrolysis reaction temperature in step S5 is 25-50℃. More preferably, the hydrolysis reaction temperature in step S5 is 25℃, at which temperature the hydrolysis reaction is more uniform, resulting in smaller and more uniform nanoparticles in the final gel.
[0019] Preferably, the volume ratio of the silicon source in step S1 to the catalyst in step S6 is 1:0.1-0.5. More preferably, the volume ratio of the silicon source in step S1 to the catalyst in step S6 is 1:0.1. At this ratio, the gel skeleton is formed to be relatively soft, so the skeleton shrinks more after drying, has higher density, and lower surface roughness.
[0020] Preferably, the catalyst in step S6 is an acid or a base. More preferably, the catalyst in step S6 is HF, HCl, or concentrated ammonia.
[0021] Preferably, in step S3, the concentration of aluminum in the alumina solution is detected using an inductively coupled plasma optical emission spectrometer (ICP-OES).
[0022] Preferably, in step S7, the drying temperature is 25-100℃ and the calcination temperature is 1100℃.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) This invention obtains an alumina solution through centrifugation. Utilizing the extremely low solubility and high dispersion of alumina in water, the alumina aqueous solution simultaneously serves as both a trace aluminum dopant source and a hydrolysis reaction chamber. This allows the silicon source to continuously combine with the alumina in the water during the hydrolysis reaction, ensuring the uniform dispersion of Al-containing functional groups in the solution and preventing other aluminum sources from directly hydrolyzing to form alumina particles or aggregates during dissolution. Furthermore, it reduces the need for high-precision instruments during the aluminum source material weighing stage, improving sampling accuracy and stability.
[0025] (2) Using an inductively coupled plasma spectrometer, the aluminum content in the alumina solution is accurately detected before doping, so as to ensure that the aluminum content in the quartz sand is within the required range by concentrating or diluting the alumina solution and controlling the amount of alumina solution added, thereby improving the accuracy and controllability of the aluminum doping amount in the sample.
[0026] (3) In step S7, by replacing the solvent in the gel and unifying the liquid composition inside the gel, the shrinkage uniformity of the gel skeleton structure during the drying stage can be effectively improved, thereby reducing the porosity inside the final quartz sand. In addition, replacing the liquid inside the gel with a highly volatile organic solvent is more conducive to improving the drying efficiency and reducing the time consumption of the entire synthesis process. Attached Figure Description
[0027] Figure 1 This is a photograph of the silica gel in Example 1 of the present invention.
[0028] Figure 2 This is a photograph of the silica dry gel in Example 1 of the present invention.
[0029] Figure 3 This is a microstructure diagram of the surface of silica dry gel particles characterized by scanning electron microscopy (SEM) in Example 1 of the present invention.
[0030] Figure 4 These are photographs and SEM images of the silica dry gel particles obtained under different hydrolysis reaction conditions in Example 2 of the present invention.
[0031] Figure 5 The images shown are SEM images of the surface morphology of silica dry gels obtained under different hydrolysis reaction conditions in Example 2 of this invention.
[0032] Figure 6 The images show optical microscopic characterizations of quartz particles obtained under different solvent substitution, drying, or calcination conditions in Example 3 of this invention.
[0033] Figure 7 This is a photograph of the quartz sand in Example 4 of the present invention.
[0034] Figure 8 This is a SEM image of the microstructure and surface morphology of the quartz sand in Example 4 of the present invention.
[0035] Figure 9 This is a distribution map of elements measured by an energy dispersive spectrometer (EDS) in quartz sand in Example 4 of the present invention.
[0036] Figure 10 The XRD test results are for quartz sand sample 4 in Example 5 of the present invention.
[0037] Figure 11 This is a photograph of the silica gel in Example 6 of the present invention.
[0038] Figure 12 This is a photograph of the silica dry gel in Example 6 of the present invention.
[0039] Figure 13 The image shows the microstructure and surface morphology of the silica dry gel in Example 6 of this invention, as represented by SEM images.
[0040] Figure 14 This is an optical microscope characterization image of the quartz particles in Example 7 of the present invention.
[0041] Figure 15 This is a photograph of the quartz sand in Example 7 of the present invention.
[0042] Figure 16 The image shows the microstructure and surface morphology of the quartz sand in Example 7 of this invention, as represented by SEM images.
[0043] Figure 17 This is an elemental distribution diagram of the quartz sand in Example 7 of the present invention. Detailed Implementation
[0044] Example 1:
[0045] This embodiment relates to a method for preparing quartz using the TEOS sol-gel method, the specific process of which includes the following steps:
[0046] (1) Using ethanol as a dispersant, take 10 mL of tetraethyl orthosilicate (TEOS) and 10 mL of ethanol, mix them and stir evenly to prepare a precursor solution.
[0047] (2) At 25°C, add 10 mL of ultrapure water to the precursor solution and continue stirring for 1 h. During this process, the silicon source will undergo hydrolysis to form silica sol.
[0048] (3) Add 1 mL of HF to the silica sol to catalyze the hydrolysis reaction and continue stirring;
[0049] (4) After stirring for 1 minute, let it stand until the polycondensation reaction is complete. Then, age the resulting gel for 30 minutes to obtain the desired product. Figure 1 silica gel;
[0050] (5) The prepared silica gel was placed in a 100°C forced-air oven for 6 hours to dry, obtaining the desired product. Figure 2The silica dry gel shown;
[0051] (6) The microstructure of the dried silica dry gel was characterized by SEM (see...). Figure 3 ).
[0052] Results and Analysis:
[0053] The microstructure of the dried silica dry gel is a dense structure formed by the accumulation of nanoparticles. The overall surface is relatively smooth, but it also exhibits a certain degree of roughness.
[0054] Example 2:
[0055] Based on the process of Example 1, the ratio of ethanol, water and catalyst, the duration and temperature of step (2) were controlled. The prepared samples were characterized by SEM to analyze the effects of the amount of dispersant, catalyst and water and reaction conditions on the obtained silica gel nanoskeleton.
[0056] (1) 10 mL of ethanol, 20 mL of water and 1 mL of HF were used to synthesize silica gel;
[0057] (2) 10 mL of ethanol, 40 mL of water and 1 mL of HF were used to synthesize silica gel;
[0058] (3) 10 mL of ethanol, 10 mL of water and 5 mL of HF were used to synthesize silica gel;
[0059] (4) Based on the formulation of Example 1, the temperature of the precursor and sol was maintained at 50°C to synthesize silica gel;
[0060] (5) Based on the formulation of Example 1, the stirring process in step (2) was extended to 5 hours to synthesize silica gel;
[0061] (6) The silica gels prepared in Examples 1 and 2 were sampled by SEM testing and then rapidly dried;
[0062] (7) The dried silica dry gel was subjected to SEM analysis to characterize its microstructure (see [reference]). Figure 4 ) and surface morphology (see Figure 5 ).
[0063] Results and Analysis:
[0064] according to Figure 4 and Figure 5SEM characterization results were used to analyze the effects of dispersant dosage, water dosage, catalyst dosage, hydrolysis temperature, and hydrolysis time on particle size, gel skeleton, and particle surface microstructure during hydrolysis. Comparison revealed that increasing water dosage and hydrolysis time resulted in smaller nanoparticles, a finer gel skeleton, and a smoother dried gel particle surface. Decreasing water dosage and increasing hydrolysis temperature led to uneven hydrolysis, resulting in significant and large differences in particle size. Adding catalyst resulted in a more rigid gel skeleton, leading to less shrinkage after drying, lower density, and higher surface roughness.
[0065] Example 3:
[0066] To ensure uniform particle size and compact overall structure, and considering experimental efficiency and equipment requirements, silica gel was synthesized according to the formulation in Example 1. The transformation of silica gel to quartz was then carried out under different solvent substitution, drying, and calcination conditions.
[0067] (1) The silica gel was replaced with ethanol for 7 days and then air-dried at room temperature to prepare quartz particles.
[0068] (2) The silica gel was replaced with ethanol for 7 days and then heated and air-dried to prepare quartz particles.
[0069] (3) The silica gel was heated and air-dried, and then calcined at 1100℃ for 3h to prepare quartz particles;
[0070] (4) The silica gel was replaced with ethanol 7 times over 7 days, heated and air-dried, and calcined at 1100℃ for 3 hours to prepare quartz particles.
[0071] (5) The silica gel was replaced with ethanol three times over three days, heated and air-dried, and calcined at 1100℃ for 3 hours to prepare quartz particles.
[0072] (6) The quartz particles prepared under different solvent substitution, drying, and calcination conditions were characterized by optical microscopy to observe their surface morphology, bubble distribution, and pore structure (see...). Figure 6 ).
[0073] Results and Analysis:
[0074] according to Figure 6The optical microscope images of the quartz particles, when compared, show that room temperature air drying has a weak effect on density, thus easily resulting in a large number of pores in the quartz particles. Heating and drying further reduces the spacing between particles, causing the micropores and voids in the gel to gradually close. If the solvent is not replaced, uneven evaporation due to different solvent components will cause uneven shrinkage of the quartz particles, resulting in a large number of tiny pores inside the quartz particles. A thorough replacement process can greatly reduce the internal pores. To improve efficiency, appropriately reducing the number of replacements can also keep the internal pore content of the quartz particles within an acceptable range. The calcination process not only gradually closes the internal micropores and voids through thermal shrinkage of the material, but also promotes the detachment of hydroxyl groups on the gel skeleton, thereby further reducing the bubble content inside the quartz particles.
[0075] Example 4:
[0076] Based on the quartz preparation process of Examples 1-3, using alumina aqueous solution as both the aluminum and water source, trace aluminum-doped quartz sand was prepared:
[0077] (1) Take 10 mL of TEOS and 10 mL of ethanol, mix them and stir well to prepare the precursor solution;
[0078] (2) Weigh 1g of alumina powder and place it at the bottom of a 50mL centrifuge tube;
[0079] (3) Add 45 mL of ultrapure water to the centrifuge tube and centrifuge twice at 3000 rad / min for 30 minutes. Take the upper suspension and centrifuge again at 3000 rad / min for 30 minutes. Filter the supernatant after centrifugation through a filter membrane (10 μm, the same below) to obtain an alumina solution.
[0080] (4) Take 10 mL of alumina solution and test it using ICP-OES. Based on the measured results (Al concentration is 44 ppm, see Table 1), the target doping amount (10 ppm), and the volume of alumina solution added in the hydrolysis reaction (40 mL), calculate the dilution factor of the alumina solution and dilute the concentration of the alumina solution.
[0081] (5) Add 40 mL of diluted alumina solution to the precursor solution to carry out the hydrolysis reaction;
[0082] (6) After stirring for 30 minutes, add 1 mL of hydrofluoric acid to the precursor solution to gel it.
[0083] (7) After the gel ages, replace it three times with ethanol;
[0084] (8) After replacement and impurity removal, the gel is placed in a constant temperature oven at 35°C for drying to form a dry gel;
[0085] (9) The dry gel was placed in a muffle furnace and sintered at a high temperature of 1100℃ for 3 hours to densify it and form quartz particles.
[0086] (10) The quartz particles are crushed and ground to obtain the following: Figure 7 The quartz sand shown;
[0087] (11) Samples of the prepared quartz sand were taken and subjected to SEM testing to characterize its microstructure (see Figure 8 );
[0088] (12) Weigh 0.30g of the prepared quartz sand and add 3mL of HF for digestion;
[0089] (13) After digestion, add ultrapure water to dilute it to 26.07g and perform ICP-OES test (see Table 2);
[0090] (14) Samples of the prepared quartz sand were taken and EDS tests were performed (see results). Figure 9 ).
[0091] Table 1. ICP-OES test results of the alumina solutions used in Examples 4 and 5.
[0092] Analyte (Measure Mode) Concentration average P 185.942(Aqueous-Axial-iFR) 0.011ppm Ni 231.604 (Aqueous-Axial-iFR) 0.010ppm B 249.773(Aqueous-Axial-iFR) 0.036ppm Mn 257.610(Aqueous-Axial-iFR) 0.012ppm Fe 259.940 (Aqueous-Axial-iFR) 0.043ppm Ge 265.118(Aqueous-Axial-iFR) 0.001ppm Mg 279.553 (Aqueous-Axial-iFR) 3.844ppm Cr 283.563 (Aqueous-Axial-iFR) 0.002ppm Cu 324.754 (Aqueous-Axial-iFR) 0.010ppm Ti 334.941(Aqueous-Axial-iFR) 0.002ppm Zr 339.198(Aqueous-Axial-iFR) 0.000ppm Ca 393.366 (Aqueous-Axial-iFR) 17.854ppm Al 396.152 (Aqueous-Axial-iFR) 44.281ppm Ba 455.403 (Aqueous-Axial-iFR) 0.069ppm Na 588.995 (Aqueous-Axial-iFR) 14.373ppm Li 670.784(Aqueous-Axial-iFR) 0.005ppm K 766.490(Aqueous-Axial-iFR) 5.979ppm
[0093] Table 2. ICP-OES test results of aluminum-doped quartz sand
[0094]
[0095]
[0096] Results and Analysis:
[0097] according to Figure 8 The SEM images obtained show that the quartz sand prepared by this process is formed by the first aggregation of nanoparticles into clusters, and then through cluster stacking or cross-linking. Compared with the dry gel microstructure before calcination, the difference in surface micromorphology is small. The surface of the quartz sand is still relatively smooth and has a certain degree of roughness. However, the size of the particles inside the quartz particles has increased, and the cross-linking between particles appears to be more compact and firm. This is mainly because the free energy of the particle surface decreases under high temperature, thus gradually fusing and forming larger and more stable particles. The thermal shrinkage during the sintering process reduces the spacing between particles, and the effect of silicon-oxygen bonds and the interaction between particles are enhanced, ultimately resulting in a more compact and firm cross-linking of the overall microstructure.
[0098] Based on the ICP-OES test results, and using the formula
[0099]
[0100] Among them, c (sample) c represents the percentage of elements present in the sample. (test) To determine the corresponding elemental concentrations in the diluted test solution, m (sample) m is the mass of the sample taken. (test) To determine the mass of the diluted test solution, based on the data measured in Table 2, the Al content in the quartz particles was calculated using this formula to be 9.73 ppm.
[0101] ICP-OES test results confirmed the successful doping of Al in the quartz particles. To verify the uniformity of the doping, elemental distribution tests were performed on the sample (see...). Figure 9 The results show that no aluminum particles or clusters were detected, and the Al in the sample was uniformly distributed and dispersed.
[0102] Example 5:
[0103] This embodiment is based on the synthesis process of Example 4, but changes the amount of alumina added in steps (4) and (5). 200 μL, 1.50 mL, 3.00 mL and 14.0 mL of alumina solution with an Al content of 44 ppm were taken and diluted to 40 mL to prepare a series of quartz sands with different aluminum doping amounts. The prepared samples were tested by ICP-OES (see Table 3). According to the doping concentration, sample 4 with the highest doping concentration was selected for X-ray diffraction (XRD) test to analyze the effect of doping on the phase of quartz sand.
[0104] Results and Analysis:
[0105] High-purity quartz sand with different aluminum doping levels was prepared by adjusting the concentration of the alumina solution. The aluminum doping level in the samples was calculated based on the measured sample mass, the mass of the diluted test solution, and the aluminum content in the test solution (see Table 4). The results show that this process can control the aluminum doping level in high-purity quartz sand within the range of 3-228 ppm by adjusting the concentration of the alumina solution.
[0106] Table 3 shows the ICP-OES test results of Al-doped quartz sand with different doping concentrations in Example 5.
[0107]
[0108] Table 4 shows the actual Al content of Al-doped quartz sand with different doping concentrations in Example 5.
[0109] sample <![CDATA[m (sample) (g)]]> <![CDATA[m (test) (g)]]> <![CDATA[c (test) (ppm)]]> <![CDATA[c (sample) (ppm) <!-- 7 -->]]> 1 0.543 34.83 0.052 3.34 2 0.669 32.49 0.485 23.55 3 0.105 45.86 0.126 55.03 4 0.225 49.37 1.041 228.42
[0110] according to Figure 10The XRD results show that the trace amount of Al doping is not enough to affect the crystal phase of the quartz sand. The quartz sand with an aluminum content of 228 ppm still only exhibits the amorphous state of SiO2.
[0111] Example 6:
[0112] This embodiment is based on the above-described process of synthesizing quartz via the TEOS sol-gel method, using TMOS as the silicon source to prepare quartz sand. The specific process includes the following steps:
[0113] (1) Take 10 mL of TMOS and 10 mL of ethanol, mix them and stir evenly to prepare a precursor solution;
[0114] (2) Add 40 mL of ultrapure water to the precursor solution and continue stirring for 1 h. During this process, the silicon source will undergo hydrolysis to form silica sol.
[0115] (3) Add 1 mL of ammonia to the silica sol to catalyze the polycondensation reaction and continue stirring;
[0116] (4) After stirring for 1 minute, let it stand until the polycondensation reaction is complete. Then, age the resulting gel for 30 minutes to obtain the desired product. Figure 11 silica gel;
[0117] (5) The gel was replaced with ethanol 7 times;
[0118] (6) The replaced silica gel was placed in a 100°C forced-air oven for 6 hours to dry, obtaining a silica dry gel. Compared with the one obtained by HF catalysis, this dry gel was white rather than transparent (see...). Figure 12 );
[0119] (7) Samples of the prepared silica dry gel were taken and subjected to SEM testing (see...). Figure 13 ), which characterizes its structure.
[0120] Results and Analysis:
[0121] The silica dry gel prepared by alkaline catalysis using TMOS as the silicon source also exhibits a stacked structure formed by the aggregation of nanoparticles. Compared with the dry gel prepared by acid catalysis, its surface is smoother, but it still has a certain degree of roughness.
[0122] Example 7:
[0123] Based on the process of Example 5 and the experience gained from Example 4, trace amounts of aluminum-doped silica gel and quartz were prepared:
[0124] (1) Take 10 mL of tetramethyl orthosilicate (TMOS) and 10 mL of ethanol, mix them and stir evenly to make a precursor solution;
[0125] (2) Weigh 0.25g of alumina powder and place it at the bottom of a 50mL centrifuge tube;
[0126] (3) Add 45 mL of ultrapure water to the centrifuge tube and centrifuge twice for 30 minutes at 3000 rad / min. Extract the supernatant to obtain an alumina solution.
[0127] (4) Take 10 mL of alumina solution and test it using ICP-OES. Based on the measured results (Al concentration is 27 ppm, see Table 5), the target doping amount (5 ppm), and the volume of alumina solution added in the hydrolysis reaction (40 mL), calculate the dilution factor of the alumina solution and dilute the concentration of the alumina solution according to the calculation results.
[0128] (5) Take 40 mL of the diluted alumina dispersion and add it to the precursor solution, and stir to promote the hydrolysis reaction;
[0129] (6) After the hydrolysis reaction has been going on for 30 minutes, 1 mL of concentrated ammonia water is added to the reaction solution to carry out the condensation reaction, thereby forming silica gel, and the silica gel is aged for 2 hours.
[0130] (7) After aging, the gel was replaced with ethanol 7 times;
[0131] (8) The replaced silica gel was placed in a 100°C forced-air oven for 6 hours to dry it, and a silica dry gel was obtained.
[0132] (9) Calcine the silica dry gel at 1100℃ for 3 hours to obtain quartz particles;
[0133] (10) The quartz particles were characterized using an optical microscope, and the internal bubbles and pores were analyzed (see...). Figure 14 );
[0134] (11) The quartz particles are crushed and ground to obtain quartz sand (see Figure 15 );
[0135] (12) Samples of the prepared quartz sand were taken and subjected to SEM testing (see...). Figure 16 );
[0136] (13) Take a sample of the prepared quartz sand and weigh it. The weight is 0.373 g. Then digest it with 3 mL of HF.
[0137] (14) After digestion, the solution was diluted with ultrapure water to complete the preparation of the test solution and weighed to 39.255g.
[0138] (15) The aluminum content was tested using ICP-OES (see Table 6);
[0139] (16) Samples of the prepared quartz sand were taken and EDS mapping test results were obtained (see...). Figure 17 ).
[0140] Table 5. ICP-OES test results of the alumina solution used in Example 7.
[0141]
[0142]
[0143] Table 6 shows the ICP-OES test results of the Al-doped quartz sand prepared in Example 7.
[0144] Analyte (Measure Mode) Concentration Al 167.079 (Aqueous-Axial-iFR) 0.048ppm P 177.495 (Aqueous-Axial-iFR) -0.001ppm Ni 231.604 (Aqueous-Axial-iFR) 0.053ppm B 249.773(Aqueous-Axial-iFR) 0.071ppm Mn 257.610(Aqueous-Axial-iFR) 0.000ppm Fe 259.940(Aqueous-Axial-iFR) 0.033ppm Ge 265.118(Aqueous-Axial-iFR) -0.100ppm Mg 279.553(Aqueous-Axial-iFR) 0.011ppm Cr 283.563(Aqueous-Axial-iFR) -0.008ppm Cu 324.754(Aqueous-Axial-iFR) 0.004ppm Ti 334.941(Aqueous-Axial-iFR) 0.002ppm Zr 339.198(Aqueous-Axial-iFR) 0.001ppm Ca 393.366(Aqueous-Axial-iFR) 0.254ppm Ba 455.403(Aqueous-Axial-iFR) 0.001ppm Na 588.995(Aqueous-Axial-iFR) 0.311ppm Li 670.784(Aqueous-Axial-iFR) 0.001ppm K 766.490(Aqueous-Axial-iFR) 1.107ppm
[0145] Results and Analysis:
[0146] according to Figure 14 The optical microscopy characterization results showed that the quartz particles prepared from the silica gel synthesized by the TMOS alkaline catalysis method through solvent replacement, heating and drying, and high-temperature calcination were relatively dense internally with few bubbles and pores. Figure 16 The SEM characterization results showed that, compared with the calcined quartz particles, the porosity between the particles was reduced, the overall density of the structure was improved, and the surface was also smoother. This is similar to the analysis in Example 4.
[0147] The Al content in the quartz sand digestion and dilution solution was detected by ICP-OES to be 0.048 ppm. According to formula (1), the Al doping content in the quartz sand prepared in this embodiment was calculated to be 5.05 ppm. The elemental distribution was then tested using EDS mapping. Figure 17 The Al element still exhibits a uniformly dispersed distribution, with no large-sized Al-containing particles or clusters precipitated.
[0148] Example 8:
[0149] Based on the process of Example 7 and the experience of Example 5, using TMOS as the silicon source, multiple groups of quartz sands with different aluminum doping amounts were prepared by changing the target doping amounts to 5ppm, 7.5ppm, 12.5ppm, and 15ppm. The Al content in the prepared quartz sand was analyzed by sampling, digestion, and ICP-OES testing (results shown in Table 7).
[0150] Table 7. ICP-OES detection results of Al-doped quartz sand in Example 8.
[0151]
[0152] Results and Analysis:
[0153] The measured ICP-OES data were converted into Al content in quartz sand using formula (1). The results are shown in Table 8. This indicates that the doping method using alumina solution as the aluminum source is also applicable to the TMOS alkaline catalytic sol-gel method, and the amount of aluminum doping can also be controlled by adjusting the amount of alumina added.
[0154] Table 8. Actual Al content of Al-doped quartz sand in Example 8
[0155] Sample <![CDATA[m (sample) (g)]]> <![CDATA[m (test) (g)]]> <![CDATA[c (test) (ppm)]]> <![CDATA[c (sample) (ppm)]]> 1 0.665 40.65 0.077 4.71 2 0.417 31.93 0.095 7.27 3 0.532 44.74 0.149 12.53 4 0.471 26.94 0.263 15.04
[0156] As shown in Examples 1-8, the developed processes allow for the preparation of quartz sand using both the TEOS acid catalysis method and the TMOS alkaline catalysis method, resulting in quartz sand with high purity, high density, and few bubbles and pores. In the trace aluminum-doped quartz sand obtained through alumina doping, the Al doping amount is controllable, and the Al element is evenly and dispersed.
Claims
1. A method for preparing high-purity quartz sand with trace amounts of aluminum doping, characterized in that, Includes the following steps: S1. Mix the silicon source and solvent evenly to obtain the precursor solution; S2. Mix alumina and ultrapure water, centrifuge, take the supernatant, and filter it through a filter membrane to obtain an alumina solution. S3. Detect the concentration of aluminum in the alumina solution; S4. Dilute the alumina solution according to the target doping amount; S5. Take the diluted alumina solution from step S4 and add it to the precursor solution obtained in step S1. Mix and stir to allow hydrolysis to occur and form a sol. S6. Add a catalyst to the sol to obtain a gel; S7. The gel is aged, and then the water in the gel is replaced with the same solvent as in step S1. The gel is dried, calcined, and ground to obtain the trace aluminum-doped high-purity quartz sand. The aluminum doping concentration in the trace aluminum-doped high-purity quartz sand is 3-229 ppm.
2. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 1, characterized in that, In step S1, the silicon source is tetramethyl or tetraethyl orthosilicate; and / or, the solvent is ethanol, methanol, or acetone.
3. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 1, characterized in that, The volume ratio of the silicon source in step S1 to the diluted alumina solution added in step S5 is 1:1-4.
4. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 3, characterized in that, The volume ratio of the silicon source in step S1 to the diluted alumina solution added in step S5 is 1:
4.
5. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 1, characterized in that, The hydrolysis reaction in step S5 is carried out at a temperature of 25-50℃.
6. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 1, characterized in that, The volume ratio of the silicon source in step S1 to the catalyst in step S6 is 1:0.1-0.
5.
7. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 6, characterized in that, The volume ratio of the silicon source in step S1 to the catalyst in step S6 is 1:0.
1.
8. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 1, characterized in that, In step S6, the catalyst is an acid or a base.
9. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 8, characterized in that, In step S2 and step S6, the catalyst is HF, HCl or concentrated ammonia.
10. The method for preparing trace amounts of aluminum-doped high-purity quartz sand according to claim 1, characterized in that, In step S7, the drying temperature is 25-100℃ and the calcination temperature is 1100℃.
Citation Information
Patent Citations
Method for processing high-strength quartz crucible for monocrystalline silicon production
CN109467306A
Aluminum-doped quartz sand and preparation method thereof
CN116715243A
